Übersetzungsäquivalente substantivierter Adjektivwörter vom Typ das Neue, das Schöne (neutrale Abstrakta) im Polnischen - KUBASZCZYK, JOANNA (Wydawnictwo Naukowe UAM, 2006)
The article discusses the translation problem of adjectives converted into nouns such as das Neue, das Moderne. There are presented results of research based on the corpus of more than 400 entities and their translations from German into Polish. The analysis used tools of Cognitive Linguistics to catch most important semantic differences between equivalents. Five types of equivalents are the most frequently chosen but only 20 per cent solutions in Polish are adjectives converted into nouns. Therefore the supposition is that these formations can be the source of difficulties for translators.
Keywords: Übersetzungsäquivalente; Adjektivwörter; Neutrale Abstrakta